A montmorillonite-modification strategy enabling long cycling stability of dual-ion batteries. Issue 80 (20th September 2022) - Li, Gen; Wang, Huanwen; Shi, Xiaojun; Yang, Caihong; Wang, Rui; He, Beibei; Jin, Jun; Gong, Yansheng; Tang, Aidong; Yang, Huaming
Abstract : Montmorillonite is employed to build a novel electrode/electrolyte interface in dual-ion batteries, which can reduce the electrolyte decomposition and maintain the structural integrity of graphite during the PF6 − -intercalation process. Abstract : Lithium‖graphite dual-ion batteries (DIBs) have received widespread attention due to their low cost and high operating voltage (nearly 5 V). However, DIBs face several challenges such as decomposition of the electrolyte under high voltage and structural deterioration of graphite. Herein, montmorillonite (MMT) is employed to generate a favorable and robust cathode electrolyte interface (CEI) layer on the graphite surface. As a result, the DIBs exhibit a 100% capacity retention for 500 cycles at 2C. Even after 1000 cycles at 5C, the capacity retention is still as high as 99%.